Теплопровiднiсть молекулярних кристалiв з безладдям, що самоорганiзується - Krivchikov, A. I.; Vdovychenko, G. A.; Korolyuk, O. A.; Romantsova, O. O. (Publishing house "Academperiodika", 2018)
The thermal conductivity of some orientational glasses of protonated C2H5OH and deuterated C2H5OH ethanol, cyclic substances (cyclohexanol C6H11OH, cyanocyclohexane C6H11CN, cyclohexene C6H10, and freon 112 (CFCl2)2 have been analyzed in the temperature interval 2–130 K. The investigated substances demonstrate new effects concerned with the physics of disordered systems. Universal temperature dependences of the thermal conductivity of molecular orientational glasses have been revealed. At low temperatures, the thermal conductivity exhibits a universal behavior that can be described by the soft potential model. At relatively high temperatures, the thermal conductivity has a smeared maximum and than decreases with increase in the temperature, which occurs typically in crystalline structures.